Occupational Exposure and Risk Factors for Musculoskeletal Symptoms Among Workers: A Literature Review - Indrayani, Ni Luh Dwi; Israfil, Israfil; Suyasa, I Gede Putu Darma; Pimsen, Apiradee (Borneo Scientific Publishing, 2026)
Early musculoskeletal (MSK) symptoms across occupations often present as strain or fatigue, which may progress into long-term disorders and contribute to global burden disease. This reviewed literature examined occupational exposures and their association with musculoskeletal (MSK) symptoms related to work using MeSH term and Emtree in structuring a framework of population, context, and concept. The population (P) included workers, the concept (C) focused on prevalence and exposure, and the context (C) addressed musculoskeletal pain, discomfort, or symptoms. Eligible studies reporting self-reported prevalence or occupational risk factors were systematically extracted and summarized. Findings among 9 articles indicated majority prevalence of MSK symptoms higher than 60% measured mostly by Nordic Musculoskeletal Questionnaire (NMQ). The highest body part major in low back and upper limbs including wrists for pink-collar, while in blue-collar workers fairly distributed in upper and lower limbs. The physical exposure mainly due to injury body weight, meanwhile psychosocial occupational exposures such as mental stress, job tenure contribute significantly to musculoskeletal symptoms (p<0.001) rather than physical exposure, with prevalence and distribution varying across body regions and occupational groups. These results emphasize the need for baseline data to guide future research based on job demands and inform targeted preventive strategies and workplace interventions.